Investigation of the Changes in Rheological Properties of Purple Basil Sherbet Samples Concentrated by Ohmic Heating at Different Voltage Gradient - Zeynep Eroğlu; Mutlu Çevik (Turkish Journal of Agriculture: Food Science and Technology)
Purple basil is widely used medicinally and aromatically due to its essential oil properties, and it is a plant that stands out with its antibacterial, antimutagenic and antioxidant properties. It has been determined that purple basil has positive effects on health such as appetizing, insomnia, sputum, diuretical and antispasmodic. Purple basil contains high concentrations of anthocyanins and with these properties it stands out as a potential new source of stable red pigments for the food industry. In recent years, it has been seen that purple basil has been processed into different products such as tea and sherbet in order to benefit from its functional properties. With the processing of purple basil into different products, it is seen that the consumption of basil and basil products has increased by consumers. In this study, purple basil sherbet samples were concentrated at different voltage gradient values (14, 17 and 20 V/cm) under atmospheric conditions with ohmic heating up to 25% soluble solid content (SSC) and the changes in their rheological properties during the concentration process was investigated. The changes in the rheological properties of the purple basil samples were determined in the range of 1-148 s-1 shear rate values and measurement temperature was 25°C. The compatibility of different rheological models (Newton, Power-Law and Herschel-Bulkley) to the experimental data was statistically evaluated to determine the flow behavior index of the purple basil sherbet samples. It has been determined that the shear stress values increased as the shear rate values increased in all the process conditions. Similarly, at the same shear rate values, it was determined that the shear stress values increased as the SSC values increased. It has been determined that the best suitable rheological model was Herschel-Bulkley Model for all purple basil sherbet concentrates. It is thought that the results obtained will provide important data to the food and machinery industry for the installation of pilot and industrial scale ohmic heating systems.